Civil society and development : Pacific Island case studies : a dissertation presented in fulfilment of the requirements for the degree of Doctor of Philosophy in Development Studies at Massey University, Palmerston North, New Zealand - Swain, Peter Mervyn (Massey University, 1999)
This enquiry set out to examine the role of civil society in economic and social development, and the relationship between the state, the market and civil society, in the island nations of the Pacific. The study also explored the notions of progress and development and identified the impact of the dominant development paradigm on traditional Pacific Island communities, cultures and economies. Case studies were undertaken of three segments of civil society in the Pacific Islands. A village community in Samoa, a non-government organisation in the Solomon Islands and a Pacific-wide social movement were the subjects of this enquiry. The study found that state-led and market-driven approaches to development have led to significant development failures in the Pacific Islands and a neglect of civil society. It is argued throughout this study, with supporting evidence from the three case studies, that civil society can and does make a significant contribution to the economic and social development of Pacific Island nations but that contribution has largely been neglected. This thesis argues that the state, the market and civil society all have important complementary roles to play in the development of a nation and, by working together in a coordinated manner, they have the capacity to improve the quality of life and create good change for people of the Pacific and their communities. It was concluded that civil society needs to assume a higher priority in development planning and practice, and that the participation of indigenous people, on their own terms, is central to good development practice. Furthermore, an explanatory model of the relationship between state, market and civil society was advanced. This model has the capacity to assist development education, policy formulation and programme planning. This study contributes to the discourse on civil society and alternative development and advances a range of proposals to improve development practice.
Keywords: Pacific Islands; Samoa; Solomon Islands; Civil society, Pacific Islands; Economic development, Solomon Islands; Economic development, Samoa; Community development, Pacific Islands; Social development, Pacific Islands